Deconstruction of the Policy for the Establishment of Houses of Worship in Indonesia - Ruslan, Idrus; Mawardi, Mawardi; Anshori, Ahmad Afnan (UIN Sunan Gunung Djati Bandung, 2022)
This study examines the conflict in establishing houses of worship in Indonesia and the problems faced with PBM policies No. 9 and 8 of 2006. This research is purely a literature study using a qualitative approach. The government guarantees freedom of religion and performs worship according to their religion. Unfortunately, in PBM Numbers 9 and 8 of 2006, the policy of establishing houses of worship in its implementation takes work. The problem of establishing places of worship occurs due to the government's need for more socialization with the public regarding policies for the establishment of houses of worship, bureaucratic policies that tend to be discriminatory, and local religious leaders. Its are not involved in Such policies can potentially lead to the dualism of authority, unclear policies can lead to multiple interpretations, and in the perspective of human rights, these policies ignore human rights. Therefore, the government needs to reorganize or deconstruct the policy for establishing houses of worship in PBM Numbers 9 and 8 of 2006 so that there will be no conflict over establishing places of worship in the future.